Exploring patterns of child-to-parent violence and abuse from caregivers’ perspectives: parental experiences, correlates and support-seeking behaviour - Turner, Katie (2020)
Background: Child-to-parent violence and abuse (CPVA) is recognised as a form of domestic violence (DV). However, little is known about its prevalence, associations with other types of DV, or how caregivers cope with this behaviour.